Assessment of gonadal maturation by evaluation of spermaturia. Issue 11 (November 1990) - Schaefer, F; Marr, J; Seidel, C; Tilgen, W; Schärer, K
Abstract : The urinary excretion of spermatozoa (spermaturia) reflects the achievement of exocrine testis function during male puberty. In order to test the sensitivity and practicability of repetitive urine sampling, we analysed the sediments of 1160 first morning urine specimens obtained on successive days from 129 healthy schoolboys aged 10.1 to 17.8 years for the presence of spermatozoa. The proportion of subjects with sperm positive urines increased from pubic hair stage (PH) 1 (6%) to PH 5 (92%) with a steep rise between PH 2 and 3. Estimated median age of first positive spermaturia ('spermarche') was 14.1 years. While at PH 1 to 4 all positive samples were found within the first five days of collection, at PH 5 cumulative frequency of spermaturia increased up to day 8. We conclude that repetitive morning urine sampling is a useful tool in assessing spermaturia and may be helpful to screen for testicular damage in epidemiological surveys.